PERAN FRONT OFFICER DALAM PENINGKATAN KEPUASAN TAMU DI QUEST HOTEL SIMPANG LIMA SEMARANG - Puput Pujonarko; Andhi Supriyadi (Media Bina Ilmiah, 2025)
This study aims to determine the role and operational challenges faced by the Front Office at Quest Hotel Simpang Lima Semarang, along with recommendations for improvement based on research findings. The main focus is on improving Front Office services to improve guest satisfaction. In this study, data was collected through observation, interviews, and documentation. The data analysis method uses triangulation, namely source triangulation, technique triangulation, time triangulation. The results of the study, the Role of Front Officers in Improving Guest Satisfaction at Quest Hotel Simpang Lima Semarang has been running well, however, there are still some obstacles in managing emotions, slow hotel systems. However, with collaboration, training, communication between departments, and HR Training Quest Hotel Simpang Lima Semarang can help in meeting guest satisfaction.